Analisis Pemberian Upah Terhadap Kinerja Karyawan di Usaha Konveksi Wijaya Tulungagung dalam Perspektif Ekonomi Islam - Moch. Uzeir Mustaqfirin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
In this study, researchers tried to find out from an Islamic point of view about the provision of wages to the performance of employees in the Wijaya Tulungagung convection business. Using a qualitative approach to research results, namely: 1) Motivating factors considered employee performance in the Wijaya Tulungagung Convection business are salaries, needs, expectations regarding rewards and relationships with business owners, 2) The implementation of wages is by wages according to the period of time and achievement. Wages by term of time are those who work at the stages ofbriing, breaking, cleaning, tidying clothes, but they usually take wages on weekends. While wages according to achievement are at the stage of tailoring, ironing clothes and cutting cloth, 3) The criteria for giving wages are based on the work they do in the Wijaya Tulungagung Convection business such as sewing wages different from the wages of breaking, the wages of cloth mottos are different from the ironing wages of clothes and pants, 4) In the Islamic economic perspective the performance of employees in the Wijaya Tulungagung Convection business is the provision of rewards( rewards), the recommendation in motivating employees to improve work ethic.